ABOUT THE ISSUE OF CARBIDES FE3C AND FE7C3 FORMATION IN HIGH-CHROMIUM CAST IRONS - Netrebko, V. V. (Science and Transport Progress, 2016)
Purpose. This article analyzes the formation conditions, transformation and systematization of carbide phases formed in the system Fe – C – Cr.Methodology. Conversion of the elements’ content from mass % into atomic % and vice versa was carried out using standard methods. In order to identify the structural components and etching of carbides the Marble etchant was applied. Cast iron 300Х28Н2 in cast state without heat treatment and after isothermal holding at 1050 °С during 4.5 hours with further normalization was studied. Findings. Isothermal state diagrams of the Fe–C–Cr system don’t take into account the existence of Fe7C3 carbide alloyed with chromium. But there is evidence of the existence of chromic carbides containing 24…37.6 % of chromium, which exceeds its maximum solubility in cementite, but is not enough to form Cr7C3.Analysis of chromium and carbon content in carbide phases which are formed in high-chromium cast irons allowed to substantiate the formation of Fe7С3 carbide, stabilized with chromium. Assessment of the carbide phase by chemical composition in mass percent doesn’t allow determining the main carbide-forming element with sufficient accuracy. It is shown that with the increase of chromium concentration in carbides, mass content of carbon increases. Areas of existence of carbides of different types depending on carbon and chromium content in them were determined. Maximum content of chromium in the carbide (Fe, Cr)7C3 is 44.0 %. Allocation of alloyed cementite occurs on the present carbides Ме7C3 or grain boundaries, and with the increase of cooling rate – in the grain volume. This process is thermodynamically inevitable due to the decrease of carbon solubility in ferrite or austenite at temperatures when chromium diffusion is impeded, and only carbon diffusion is possible. At high chromium concentrations carbide Fe7C3 is formed, which transforms into Cr7C3 carbide as chromium diffusion takes place. Originality. The model of laminated structure of carbides, formed out of the liquid phase in the system Fe–C–Cr was built. The identification of the carbide phase based on the elements’ concentration in atomic percent was suggested. The model of the change of carbon content in carbides of different types depending on chromium concentration was built. Practical value. The suggested system of carbide classification and their structural model allows optimizing the cast irons’ composition and heat treatment modes for different exploitation conditions.